2020
DOI: 10.1371/journal.pone.0242263
|View full text |Cite
|
Sign up to set email alerts
|

Identification of prognostic genes in uveal melanoma microenvironment

Abstract: Background Uveal melanoma (UM) is the most common primary intraocular malignancy in adults. Many previous studies have demonstrated that the infiltrating of immune and stromal cells in the tumor microenvironment contributes significantly to prognosis. Methods Dataset TCGA-UVM, download from TCGA portal, was taken as the training cohort, and GSE22138, obtained from GEO database, was set as the validation cohort. ESTIMATE algorithm was applied to find intersection differentially expressed genes (DEGs) among tu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 77 publications
3
29
0
2
Order By: Relevance
“…It is consistent with previous studies that CD8+ T cell refers to favorable prognosis in CM and predicts poor prognosis in UM (Azimi et al, 2012;Gartrell et al, 2018;Wang et al, 2020). Besides, Luo et al recently identified several prognostic genes in UM, and almost every gene was correlated with abundance in CD8+ T cell (Luo and Ma, 2020). Hence, it is urgent to explore the adaptive immune response gene signature to improve the effect of tumorinfiltrating CD8+ T cell targeting approaches and the response of immunotherapies in UM.…”
Section: Discussionsupporting
confidence: 86%
“…It is consistent with previous studies that CD8+ T cell refers to favorable prognosis in CM and predicts poor prognosis in UM (Azimi et al, 2012;Gartrell et al, 2018;Wang et al, 2020). Besides, Luo et al recently identified several prognostic genes in UM, and almost every gene was correlated with abundance in CD8+ T cell (Luo and Ma, 2020). Hence, it is urgent to explore the adaptive immune response gene signature to improve the effect of tumorinfiltrating CD8+ T cell targeting approaches and the response of immunotherapies in UM.…”
Section: Discussionsupporting
confidence: 86%
“…Contrary to what is found in other tumors, lymphocytic infiltration is related to poor prognosis. In a similar vein, a study by Luo and Ma [ 22 ] in UM also associated CD8 lymphocytic infiltration with poor prognosis (univariate analysis), and B-cell infiltration with better prognosis (multivariate analysis). This association between inflammation and poor prognosis in uveal melanoma has already been described in individual studies [ 14 , 23 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 68%
“…While our results need further verification in different experimental settings, the CIBERSORTx algorithm we employed has been extensively validated with techniques such as flow cytometry, mass cytometry, immunohistochemistry, and single-cell RNA-seq by multiple different groups, providing robust data confirming its accuracy [40,[63][64][65]. Nevertheless, others have already created mRNA/miRNA/DNA-based scores with strong prognostic values in UM tumors [33,[66][67][68][69][70][71][72]. Rather than compete with them, our foremost motive for creating the cell type-based prognostic score was to select the cell types playing a prime role in the biology of UM progression Previous research has identified extensive lymphocyte infiltration as a negative prognostic factor in UM; however, the prognostic role of individual subsets was not assessed Another dominant subset of tumor-infiltrating immune cells is macrophages.…”
Section: Journal Of Immunology Researchmentioning
confidence: 76%